Implementasi Metode Bernyanyi dalam Meningkatkan Kemampuan Komunikasi Anak Usia Dini - Hana Kamilah; Silva Sahira; Nur Fadilah; Junita Irawati (PT. Willy Print Art, 2025)
This study aims to describe in depth and detail about three main focuses, namely: (1) the implementation of the singing method by PAUD teachers in daily learning activities, including how teachers design, implement, and evaluate singing activities integrated with learning themes; (2) supporting and inhibiting factors that arise during the process of implementing the singing method, such as the availability of facilities, teacher skills, children's interests, and parental involvement in supporting children's communication processes; and (3) the impact on children's verbal and nonverbal communication skills aged 4-6 years, both in the context of vocabulary use, sentence structure, speaking courage, and expression through movements and mimics. This study uses a descriptive qualitative approach that allows researchers to explore phenomena in a naturalistic and in-depth manner. The research was conducted at PAUD [Place Name], with the research subjects consisting of PAUD teachers and early childhood children in group A aged between 4 to 6 years old. The research data were collected through direct observation of singing activities, in-depth interviews with teachers and parents, and documentation of related learning activities. All data were analysed systematically through the stages of data reduction, data presentation, and conclusion drawing, by applying triangulation of sources and techniques to increase the validity of the research findings.